Infants and children : prenatal through middle childhood - Berk, Laura E. (Boston : Allyn And Bacon, 2008)
Berk$1 (Bs signature storytelling style invites students to actively learn beside the text$1 (Bs (3z(Bcharacters(3y (Bwho share their influential experiences and developmental milestones. Students are provided with an exceptionally clear and coherent understanding of child development, emphasizing the interrelatedness of all domains$1 (Bphysical, cognitive, emotional, and social$1 (Bthroughout the text narrative and in special features. Focusing on education and social policy as critical pieces of the dynamic system in which the child develops, Berk pays meticulous attention to the most recent scholarship in the field. Berk helps students connect their learning to their personal and professional areas of interest and their future pursuits as parents, educators, heath care providers, social workers, and researchers. Theory and Research in Child Development, Foundations of Development, Infancy and Toddlerhood: the First Two years, Early Childhood: Two to Six Years, Middle Childhood: Six to Eleven Years. Child Developments
Includes bibliographical references and index.
Keywords: Child development; Enfants -- Development